(untitled) - Leonard, Peggy C (Philadelphia, Pennsylvania, 1993)
The book presents a logical, step-by-step method for learning medical terminology. It includes new anatomic, diagnostic, and surgical terms. Exercises at the end of lessons gives a chance to identify word parts and combine them to form the terms encoutered in daily practice. It also presents a variety of crossword puzzles, multiple-choice questions, fill-in-the-blank questions, labeling exercises, case studies, and word pronunciation
Keywords: Human anatomy,Medicine,Nomenclature; Terminology,Terminoloy